Pengembangan Sistem Informasi Peminjaman Dan Pengembalian Buku Menggunakan Pendekatan V-Model (Studi Kasus: Perpustakaan Sman 1 Batu Hampar - Hanifah, Puja; Darmayanti Br Pasaribu, Rantika; Syaliman, Khairul Umam (Journal of System & Technology (SYSTEC), 2025)
The library is an important facility in supporting the teaching and learning process in the school environment. At SMA Negeri 1 Batu Hampar, recording of borrowing and returning books is still done manually, which often causes delays and recording errors. To overcome this, a website-based library information system was developed using the Laravel framework and the V-Model method to ensure the development process is carried out in a structured manner and according to user needs. The test results showed that the system ran well, where Black Box Testing with 52 test cases was successful without significant obstacles, Integration Testing showed that all features were well connected, and User Acceptance Test (UAT) on 21 test cases by four user roles (principal, librarian, teacher, and student) was 100% successful. Usability Testing also showed an average value of 76%, with details of Learnability 79.5%, Efficiency 72%, Memorability 73.5%, Error 83%, and Satisfaction 72%. With these results, the system is proven to be able to improve the work efficiency of librarians and provide easy access for users, and is suitable for implementation in the school environment.